1989
DOI: 10.1002/1097-0142(19890901)64:5<1007::aid-cncr2820640506>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tamoxifen and estrogen receptor status on survival in gastric carcinoma

Abstract: One hundred patients were entered in a randomized, controlled study of adjuvant tamoxifen therapy in gastric carcinoma. Estrogen receptor status was established by an immunohistologic method (ERD5) and 55.8% of the tumors were positive. Tamoxifen had no overall effect on survival, but there was a significant decrease in the survival time of the patients with ERD5-positive tumors. Estrogen receptor status (by the ERD5 method) is an independent prognostic factor in gastric cancer. Tamoxifen therapy does not prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 11 publications
2
31
1
Order By: Relevance
“…A pooled analysis of three studies in Scandinavia found a nonsignificantly, but nearly three-fold increased risk of gastric cancer (Rutqvist et al, 1995), and correspondingly elevated risks have been found also in other studies (Andersson et al, 1991;Curtis et al, 1996;Matsuyama et al, 2000). Finally, a trend of decreased survival among patients with gastric cancer who had been treated with tamoxifen and in whom the gastric cancer was positive for oestrogen receptors was observed in a randomised trial (Harrison et al, 1989). Although, taken together, all these previous studies suggest that tamoxifen might play a role in the aetiology of gastric adenocarcinoma, the association has not been established.…”
Section: Discussionmentioning
confidence: 79%
“…A pooled analysis of three studies in Scandinavia found a nonsignificantly, but nearly three-fold increased risk of gastric cancer (Rutqvist et al, 1995), and correspondingly elevated risks have been found also in other studies (Andersson et al, 1991;Curtis et al, 1996;Matsuyama et al, 2000). Finally, a trend of decreased survival among patients with gastric cancer who had been treated with tamoxifen and in whom the gastric cancer was positive for oestrogen receptors was observed in a randomised trial (Harrison et al, 1989). Although, taken together, all these previous studies suggest that tamoxifen might play a role in the aetiology of gastric adenocarcinoma, the association has not been established.…”
Section: Discussionmentioning
confidence: 79%
“…52 Further evidence was provided in a randomised control trial that ER positivity conferred a worse prognosis but disappointingly the administration of tamoxifen at therapeutic concentrations did not prolong survival. 53 Conversely, more recent evidence suggests that patients treated with tamoxifen may have an overall increased risk of development of gastric carcinoma and a shorter latency period between the diagnosis of breast and gastric cancer. 54 A Chinese group 55 hypothesised that, since the amplification of c-erbB-2 oncogene 56 and its overexpression had been implicated in the advancement of gastric carcinoma, and estrogen was known to inhibit its expression in breast cancer cell lines, perhaps estrogen itself could be administered as a reasonable therapeutic option for the treatment of gastric cancer.…”
Section: Estrogen and Gastric Cancermentioning
confidence: 99%
“…The prognostic significance of receptor expression is the subject of conflicting reports and remains unclear (Tokunaga et al, 1986;Yozozaki et al, 1988;Harrison et al, 1991). Clinical studies of the efficacy of adjuvant endocrine therapy, mainly involving the administration of tamoxifen, have also been inconclusive, and many studies too small and poorly controlled (Kitaoka, 1983;Kojima and Takahashi, 1986;Harrison et al, 1989b). Nevertheless, determination of sex hormone receptor expression in gastric cancer may play an important role in the understanding of the biochemical and pathophysiological behaviour of this disease.…”
mentioning
confidence: 99%